Cryptic species Hydatigera kamiyai and other taeniid metacestodes in the populations of small mammals in Serbia - Milan Miljević; Marija Rajičić; Gérald Umhang; Branka Bajić; Olivera Bjelić Čabrilo; Ivana Budinski; Jelena Blagojević (Parasites & Vectors, 2023)
Abstract Background Hydatigera (Cestoda: Taeniidae) is a recently resurrected genus with the description of a new species, Hydatigera kamiyai, a cryptic entity within the Hydatigera taeniaeformis species complex. Rodents are intermediate hosts and correct taxonomic identification of H. taeniaeformis sensu lato (s.l.) species is difficult without the use of molecular methods. The aim of this study was to identify and explore the genetic diversity of Hydatigera and other taeniid species. Methods Ten different small mammals species (856 individuals) (Rattus rattus, three Apodemus, three Arvicolinae and three Soricidae species) were examined from 2013 to 2023. Captured animals were visually examined for cysts and visible lesions. Two markers were used for amplification and sequencing: cox1 and 12S rDNA. Results Molecular analysis of cysts and visible lesions revealed four taeniid species: Hydatigera kamiyai, H. taeniaeformis sensu stricto (s.s.), Taenia martis and T. crassiceps. Hydatigera kamiyai was found in Apodemus flavicollis, A. agrarius, Microtus arvalis and Crocidrua leucodon, while H. taeniaeformis s.s. is registered in R. rattus. Hydatigera kamiyai cox1 sequences clustered with European populations and showed at least 25 nucleotid differences compared to Asian, African, Australian and one of our isolates of H. taeniaeformis s.s acquired from a rat, followed by large sequence distances (9.4% to 12.9%), indicating clear molecular distinction of two species. Conclusions This is one of the few mitochondrial gene-based studies performed after the description of cryptic entities within the Hydatigera taeniaeformis s.l. complex and represents a valuable contribution to understanding of genetic diversity, host suitability and geographic distribution of these tapeworm species. Also, our study provides an important basis of molecular data from this part of Europe for further studies. We emphasize the importance of additional studies of intermediate hosts, especially rats from Europe and Apodemus spp. and voles from ...